2014
DOI: 10.1002/jbm.a.35173
|View full text |Cite
|
Sign up to set email alerts
|

Effects of calcium phosphate composition in sputter coatings onin vitroandin vivoperformance

Abstract: Calcium phosphate (CaP) ceramic coatings have been used to enhance the biocompatibility and osteoconductive properties of metallic implants. The chemical composition of these ceramic coatings is an important parameter, which can influence the final bone performance of the implant. In this study, the effect of phase composition of CaP-sputtered coatings was investigated on in vitro dissolution behavior and in vivo bone response. Coatings were prepared by a radio frequency (RF) magnetron sputtering technique; th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 50 publications
0
26
0
Order By: Relevance
“…Investigation of the elemental composition of the HA layer showed that the Ca/P ratio was only slightly higher than that of stoichiometric HA. The ideal Ca/P ratio is dependent on the desired application, and has been investigated in a recent study, showing a trade off between short term bone regeneration and long-term stability [27]. The results of this study indicated appropriate adjustment of the secondary ion beam was achieved with minimal preferential re-sputtering of atoms with higher sputtering factors such as P–a typical finding in sputtered HA films deposited in vacuum [23,28].…”
Section: Discussionmentioning
confidence: 76%
“…Investigation of the elemental composition of the HA layer showed that the Ca/P ratio was only slightly higher than that of stoichiometric HA. The ideal Ca/P ratio is dependent on the desired application, and has been investigated in a recent study, showing a trade off between short term bone regeneration and long-term stability [27]. The results of this study indicated appropriate adjustment of the secondary ion beam was achieved with minimal preferential re-sputtering of atoms with higher sputtering factors such as P–a typical finding in sputtered HA films deposited in vacuum [23,28].…”
Section: Discussionmentioning
confidence: 76%
“…HA coating showed bands at 575, 670, 970, 1050, and 1090 cm –1 (stretching and bending motion of phosphate). 20 These P–O bonds of calcium phosphate appear sharper after heat treatment. Furthermore, the β-TCP coating spectrum presented bands in the same regions as HA coatings (575, 670, 970, 1050, and 1090 cm –1 ), characteristic of stretching and bending motion of phosphate.…”
Section: Resultsmentioning
confidence: 99%
“…There is a vast amount of evidence that CaP biomaterials with osteogenic properties have enormous potential in bone healing, reducing the chances of complications and time to repair. Urquia Edreira et al 20 evaluated the effect of CaP sputter-coatings with different phase composition in an in vitro and in vivo study. Their data demonstrated that the differences in physicochemical properties of the coatings affect both in vitro and in vivo results.…”
Section: Introductionmentioning
confidence: 99%
“… [ 120 ] α-TCP Pure Ti Magnetron sputtering Femur of rabbits : increased bone-implant contact and peri-implant bone volume with increasing coating dissolution: α-TCP > TTCP > HA (6 weeks). [ 121 ] Ti–6Al–4V Plasma spray Femur of dogs : similar bone response to TTCP and HA coatings, with a small increase in bone contact and remodeling lacunae after 5 months implantation. [ 122 ] β-TCP pure Ti Electrospray Subcutaneous implantation in goats : gradual degradation (12 weeks); [ 123 ] α+β-TCP Ti–6Al–4V PLD Rat bone marrow cells: bone matrix formation on remaining porous β-TCP coating with osteoclastic cellular resorption in the potentially osteogenic cell culture.…”
Section: Surface Biofunctions With Calcium Phosphate Coatingsmentioning
confidence: 99%